Liver gene therapy with intein‐mediated F8 trans‐splicing corrects mouse haemophilia A. Issue 6 (2nd May 2022) - Esposito, Federica; Lyubenova, Hristiana; Tornabene, Patrizia; Auricchio, Stefano; Iuliano, Antonella; Nusco, Edoardo; Merlin, Simone; Olgasi, Cristina; Manni, Giorgia; Gargaro, Marco; Fallarino, Francesca; Follenzi, Antonia; et al.
Abstract: Liver gene therapy with adeno‐associated viral (AAV) vectors is under clinical investigation for haemophilia A (HemA), the most common inherited X‐linked bleeding disorder. Major limitations are the large size of the F8 transgene, which makes packaging in a single AAV vector a challenge, as well as the development of circulating anti‐F8 antibodies which neutralise F8 activity. Taking advantage of split‐intein‐mediated protein trans ‐splicing, we divided the coding sequence of the large and highly secreted F8‐N6 variant in two separate AAV‐intein vectors whose co‐administration to HemA mice results in the expression of therapeutic levels of F8 over time. This occurred without eliciting circulating anti‐F8 antibodies unlike animals treated with the single oversized AAV‐ F8 vector under clinical development. Therefore, liver gene therapy with AAV‐ F8 ‐N6 intein should be considered as a potential therapeutic strategy for HemA. Synopsis: Liver directed AAV‐intein mediated protein trans‐splicing results in stable therapeutic levels of F8 in mice thus representing a novel therapeutic strategy for haemophilia A. Split‐intein mediated protein trans‐splicing (PTS) allows reconstitution of large proteins via adeno‐associated viral (AAV) vectors in mouse liver. The highly secreted and active F8‐N6 (N6) variant has been adapted to fit into AAV intein vectors. A single systemic injection of AAV‐N6 intein targets liver of hemophilic mice resulting in stable therapeutic levels of F8 without eliciting anti‐F8 antibodies at the vector doses used. Abstract : Liver directed AAV‐intein mediated protein trans‐splicing results in stable therapeutic levels of F8 in mice thus representing a novel therapeutic strategy for haemophilia A.